Creating constitutions in the Eastern Caribbean - Georges, P. Telford (Central Bank of Trinidad & Tobago Port of SpainTT, 1992)
Looks briefly at the history of the legislature in Trinidad and Tobago and the development of the contry's constitution from colonial times to present day, as well as the constitutions of countries of the Eastern Caribbean. The systems of first past the post and proportional representation in Trinidad and Tobago elections are also noted.